2014
DOI: 10.3390/agriculture4020147
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Spectral Phenotyping Methods can Improve and Accelerate Cercospora Disease Scoring in Sugar Beet Breeding

Abstract: Breeding for Cercospora resistant sugar beet cultivars requires field experiments for testing resistance levels of candidate genotypes in conditions that are close to agricultural cultivation. Non-invasive spectral phenotyping methods can support and accelerate resistance rating and thereby speed up breeding process. In a case study, experimental field plots with strongly infected beet genotypes of different resistance levels were measured with two different spectrometers. Vegetation indices were calculated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…A recent study on evaluating sugar beet varieties for Cercospora resistance indicated that simple vegetation indices such as normalized difference vegetation index (NDVI), leaf water index (LWI) and Cercospora Leaf Spot Index (CLSI) could be correlated with disease severity (Jansen et al, 2014). In WSU's ongoing study, 20 (Russets) and 30 (20 Russets + 10 Chip and Specialty) potato selections/lines were screened with two replications to identify varieties resistant and susceptible to viral (potato virus Y) and early die (Verticillium wilt) diseases, respectively.…”
Section: Plant Biotic Stressmentioning
confidence: 99%
“…A recent study on evaluating sugar beet varieties for Cercospora resistance indicated that simple vegetation indices such as normalized difference vegetation index (NDVI), leaf water index (LWI) and Cercospora Leaf Spot Index (CLSI) could be correlated with disease severity (Jansen et al, 2014). In WSU's ongoing study, 20 (Russets) and 30 (20 Russets + 10 Chip and Specialty) potato selections/lines were screened with two replications to identify varieties resistant and susceptible to viral (potato virus Y) and early die (Verticillium wilt) diseases, respectively.…”
Section: Plant Biotic Stressmentioning
confidence: 99%
“…Besides UAVs or other airborne platforms, ground-based imaging systems have been evaluated in studies concerning disease assessment based on optical data [26][27][28][29][30]. In this case, the authors also focused on pathogens affecting different perennial and annual crops (e.g., Huanglongbing in citrus, cercospora leaf spot in sugarbeet, tulip breaking virus, yellow rust and fusarium head blight in wheat and barley) and tested several methods for discriminating diseased and healthy plants, or to quantify disease severity, achieving variable discriminative potential and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several UAV‐based agricultural management applications were proposed, including methods to monitor drought and nutrient stress (Berni et al., 2009; Gago et al., 2017; González‐Dugo et al., 2013; Severtson et al., 2016; Zaman‐Allah et al., 2015), to treat pests and diseases (Calderón, Navas Cortés, Lucena León, & Zarco‐Tejada, 2013; Calderón, Montes‐Borrego, Landa, Navas‐Cortés, & Zarco‐Tejada, 2014; Garcia‐Ruiz et al., 2013, Jansen, Bergsträsser, Schmittgen, Müller‐Linow, & Rascher, 2014), and to measure productivity (Bendig et al., 2015; Holman et al., 2016; Maresma, Ariza, Martínez, Lloveras, & Martínez‐Casasnovas, 2016). Although these methods were developed for UAV‐collected data, they required precise calibration in order to provide accurate information on plant status.…”
Section: Flying Closer To the Target: Navs And Mavs Open New Opportunmentioning
confidence: 99%